The use of didactic games to increase the activity of students in the course of the lesson - Saidamatova, Husnigul Kalandarsho kizi (Science and Education, 2023)
This article will talk about how to use didactic games in order to increase the activity of students in the course of the lesson. The use of games in the lesson not only increases the activity of students in the lesson, but the information taught through games is stored in the reader’s memory for a long time, the student’s interest in relation to the lesson increases. This contributes to an improvement in the quality of Education. This article also provides information about games that help the teacher achieve his goal in the lesson.